Environmental assessment and management in the food industry : life cycle assessment and related approaches - Sonesson, U.; Berlin, J.; Ziegler, F.; ScienceDirect eBooks (Oxford ; Philadelphia : Woodhead Pub., 2010)
Life cycle assessment (LCA) of production and processing in the food industry is an important tool for improving sustainability. Environmental assessment and management in the food industry reviews the advantages, challenges and different applications of LCA and related methods for environmental assessment, as well as key aspects of environmental management in this industry sector. Part one discusses the environmental impact of food production and processing, addressing issues such as nutrient management and water efficiency in agriculture. Chapters in Part two cover LCA methodology and challenges, with chapters focusing on different food industry sectors such as crop production, livestock and aquaculture. Part three addresses the applications of LCA and related approaches in the food industry, with chapters covering combining LCA with economic tools, ecodesign of food products and footprinting methods of assessment, among other topics. The final part of the book concentrates on environmental management in the food industry, including contributions on training, eco-labelling and establishing management systems. With its international team of editors and contributors, Environmental assessment and management in the food industry is an essential reference for anyone involved in environmental management in the food industry, and for those with an academic interest in sustainable food production. Reviews the advantages, challenges and different applications of LCA and related methods for environmental assessmentDiscusses the environmental impact of food production and processing, addressing issues such as nutrient management and water efficiency in agricultureExamines environmental management in the food industry, including contributions on training, eco-labelling and establishing management systems.
pt. 1. Environmental impacts of food production and processing -- pt. 2. Life cycle assessment of food production and processing -- pt. 3. Current and future applications of life cycle assessment and related approaches -- pt. 4. Environmental management in the food industry.
Includes bibliographical references and index.
Safari Books Online
Elsevier
Keywords: Food industry and trade -- Environmental aspects; Environmental management; BUSINESS & ECONOMICS -- Industries -- General; Environmental management; Food industry and trade -- Environmental aspects; Electronic books